Body, Sensuousness, Eros and the New Aesthetic Order from Schiller to Rushdie - Bădulescu, Dana (Text Matters: A Journal of Literature, Theory and Culture, 2013)
In the present article, I look into the culture-building power of Eros from Schiller’s ideas of “the aesthetic state of mind” in Letters on the Aesthetic Education of Man, through the Pre-Raphaelites’ eroticism to the nineteenthcentury fin de siècle aestheticized homoeroticism and beyond. I argue that eroticism is a reaction to the increasing sense of alienation brought about by bourgeois modernity. The “moments” and texts used to illustrate the thesis that eroticism shaped an alternative order are far from exhausting a very large list which could add nuances to the argument. The body is one of the essential aspects tackled, since eroticism cannot be conceived in its absence. The body may be an object of desire around which imagination weaves its yarn, or a blank page to be inscribed, or a danger zone, or a hypertrophied space projected by the lover’s longing for fusion. Eroticism in Salman Rushdie’s novels is the focus of my approach after a survey of some landmarks of erotic imagination. I argue that his novels are a new stage of the imagination infused by Eros. The article probes into how two centuries of aesthetic modernity have been shaped by the reality principle proposed by Schiller and how that essentially erotic model has suffered changes in time.